La cristiandad de pariacaca: pedagogía y sincretismo en el Manuscrito de Huarochirí (Crítica) - Favaron Peyón, Pedro Martín (2023)
The narratives about the huaca Pariacaca in the Huarochirí Manuscript implicitly carry some ethical reflections that reflect the Indigenous philosophical mood. Since ancestral rationality did not establish a clear separation between reason and narrative, the “uncovering” of Indigenous ethics in these stories demands a hermeneutic reading. However, recognizing that the compilation of the Manuscript implied a narrative transformation under the pressure of the Catholic clergy, we cannot take these reflections as being alien to biblical influence. Therefore, it seems more convenient to understand them as a discursive attempt, on the part of the Indigenous writer of the Manuscript and the rest of the settlers of the region, to reach a new version of the stories that would allow them to express the multiple cultural heritages that were beginning to reconfigure their identitarian imaginaries.